miR-137 inhibits the invasion of melanoma cells through downregulation of multiple oncogenic target genes - Luo, Chonglin; Tetteh, Paul W.; Merz, Patrick; Dickes, Elke; Abukiwan, Alia; Hotz-Wagenblatt, Agnes; Holland-Cunz, Stefan; Sinnberg, Tobias; Schittek, Birgit; Schadendorf, Dirk; Diederichs, Sven; Eichmüller, Stefan B. (The journal of investigative dermatology, 2013)
MicroRNAs are small noncoding RNAs that regulate gene expression and have important roles in various types of cancer. Previously, miR-137 was reported to act as a tumor suppressor in different cancers, including malignant melanoma. In this study, we show that low miR-137 expression is correlated with poor survival in stage IV melanoma patients. We identified and validated two genes (c-Met and YB1) as direct targets of miR-137 and confirmed two previously known targets, namely enhancer of zeste homolog 2 (EZH2) and microphthalmia-associated transcription factor (MITF). Functional studies showed that miR-137 suppressed melanoma cell invasion through the downregulation of multiple target genes. The decreased invasion caused by miR-137 overexpression could be phenocopied by small interfering RNA knockdown of EZH2, c-Met, or Y box-binding protein 1 (YB1). Furthermore, miR-137 inhibited melanoma cell migration and proliferation. Finally, miR-137 induced apoptosis in melanoma cell lines and decreased BCL2 levels. In summary, our study confirms that miR-137 acts as a tumor suppressor in malignant melanoma and reveals that miR-137 regulates multiple targets including c-Met, YB1, EZH2, and MITF.